The Sharing Economy at the Crossroads. A Conflict Between Social Values and Market Mechanisms - Gurashi, Romina (European Journal of Sustainable Development, 2017)
In the last few years the phenomenon of the Sharing Economy rapidly gained momentum. The reasons for this success are multiple but the most important is the tendency to faster exchanges and economic relationships both on the real and the financial market. This awareness made it essential to start the study form the crisis of the hyper-capitalism and of the concept of ownership which is being replaced with that of a more fluid sharing. In this way, we will analyze the words, the concepts and the values at the basis of the sharing economy which influence the effects this new way of acting and living has on the economies and on the socialization processes of the countries involved. In this perspective, we will also try to consider if and to what extent the sharing economy can have a positive impact on sustainable development. Keywords: Hyper-capitalism, sharing economy, sustainable development, globalization, access, socialization